CLINICAL IMPORTANCE OF DETERMINATION OF HLA-DRB1 LOCUS GENES IN RHEUMATOID ARTHRITIS - V. Guseva (SPb RAACI, 2019)
Rheumatoid arthritis (RA) is a most common autoimmune inflammatory arthritis in adults. Serological marker of RA are rheumatoid factor (RF) and antibodies to cyclic citrullinated peptide (ACCP). The main genetic factor that determine predisposition to RA is HLA-DRB1 alleles. The HLA-DRB1 locus alleles may encode a common 5-amino acid sequence called ‘shared epitope’ (SE). The aim of our study is to assess the clinical significance and occurrence of SE and HLA-DRB1 genes and to analyze the prognostic significance of these factors for RA patients. We collected a serum and DNA samples from 72 patients with RA. For genotyping of HLA-DRB1 locus “DNA-Technology” kits (Moscow, Russia) were used. HLA-DRB1 SE sequences were genotyped by real-time PCR with specific primers. Determination of ACCP in serum was performed by ELISA (Euroimmun AG, Lübeck, Germany), RF detection, by turbidimetric method. Clinical status of the disease was assessed using the RA DAS-28 Activity Index. We have obtained the following results: determination of HLA-DRB1 gene frequency in the North-West region of Russia showed that the HLA-DRB1*04 gene variant occurred at 11.4%, HLA-DRB1*01, 14.2%. HLA-DRB1*10 and HLA- DRB1*14 occured, respectively, in 0,8% and 2% of the cases. The DRB1*04 and DRB1*01 allelic variants were found in 73.6% of patients with RA, and in 43.9% of the control group. Among patients with RA, the SE gene frequency was 66.6%. SE is associated with ACCP detection and higher DAS28 index. Conclusions: The allelic variations of HLA-DRB encoding SE are associated with ACCP-positive RA in the population of the North-West region of the Russian Federation. Identification of HLA-DRB1 allelic gene variants and SE sequences in this locus serve as an additional test to specify serological diagnosis in rheumatoid arthritis.